Long-term effects of forest fragmentation on Amazonian ant communities - Vasconcelos, Heraldo L.; Vilhena, José M.S.; Magnusson, William Ernest; Albernaz, Ana Luísa Kerti Mangabeira (Journal of Biogeography, 2006)
Aim: To analyse the effects of forest fragmentation on ant communities in an Amazonian landscape that has been fragmented for over a century. Location: The region surrounding the village of Alter do Chão in the Brazilian Amazonian state of Pará (2°30' S, 54°57' W). Methods: Collection of ants and measurements of tree density were performed along transects established in eight sites in continuous forest and in 24 forest fragments surrounded by savanna vegetation. Data on size, perimeter, and degree of isolation (distance to continuous forest and distance to nearest area of forest > 5 ha) of each fragment were obtained from a georeferenced Landsat image of the study area. Results: There were significant differences in species richness and composition between fragments and continuous forest, and these differences were not related to intersite variation in vegetation structure (tree density). Fragments supported fewer ant species per plot, and these species tended to represent a nested subset of those found in continuous forests. Fragments had significantly fewer rare species and fewer ant genera. However, fragments and continuous forest had similar numbers of species that also occur in the savanna matrix (i.e. that are not forest specialists). Multiple linear regression analyses indicated that species richness and composition in the fragments are significantly affected by fragment area, but not by fragment shape and degree of isolation. More species were found in larger fragments. Main conclusions: Forest fragmentation influences the organization of ant communities in Amazonian savanna/forest landscapes. Forest fragments harboured, on average, 85% of the species found in continuous forest. That these fragments, despite their long history of isolation, support a relatively large complement of the species found in continuous forest is surprising, especially given that in some recently fragmented landscapes the proportion of species surviving in the fragments is lower. Differences in inter-fragment distance and type of matrix between Alter do Chão and these other landscapes may be involved. The fact that fragments at Alter do Chão are surrounded by a natural (rather than an anthropogenic) habitat, and that most of them are less than 300 m from another forest area, may have helped to ameliorate the adverse effects of forest fragmentation. Keywords Amazon forest, ants, area effects, distance effects, habitat fragmentation, shape effects. © 2006 The Authors.
Keywords: Ant; Community Ecology; Forest Ecosystem; Habitat Fragmentation; Species Richness; Species-area Relationship; Amazonia; Para [brazil]; South America; Formicidae